Complete chloroplast genome sequence of Elatostema dissectum (Urticaceae). Issue 1 (2nd January 2019) - Fu, Long-Fei; Xin, Zi-Bing; Wen, Fang; Li, Shu; Wei, Yi-Gang
Abstract: The complete chloroplast genome of Elatostema dissectum Wedd. was reported in this study. The cp genome was 150, 302 bp in length including two inverted repeats (IRs) of 24, 565 bp, which were separated by LSC and SSC of 83, 998 bp and 17, 174 bp, respectively. The GC content was 36.2%. The genome encoded 112 functional genes, including 79 protein-coding genes, 29 tRNA genes, and 4 rRNA genes. This plastid genome is the first report for the tribe Elatostemateae in Urticaceae, which will be useful data for developing markers for further studies on resolving the relationship within the genus and tribe.